Do people with mental health problems have lower adherence to precautionary measures in COVID-19 pandemic? A cross-sectional observational study in Hong Kong - Allen T C Lee; Gabriel W H Cheng; Cuichan Lin; Brian H C Wong; Linda Chiu Wa Lam (BMJ Open)
Objectives Mental health problems are prevalent during the COVID-19 pandemic, but their effect on adherence to precautionary measures is not well understood. Given that psychological morbidities are associated with lower treatment adherence, and that precautionary measures are important in containing the spread of COVID-19, this study aims to determine if people with mental health problems have lower adherence to precautionary measures against COVID-19.Design We conducted a cross-sectional territory-wide online survey between 17 June and 31 July 2020 during the COVID-19 pandemic. Clinically significant mental health problems, adherence to precautionary behaviours, and confounding factors such as sociodemographic factors and self-reported physical health were assessed.Setting The link to the questionnaire was disseminated to the general population in all 18 districts of Hong Kong using various social media platforms.Participants 1036 individuals completed the survey. Of them, 1030 met the inclusion criteria of being adult Hong Kong residents.Primary outcome Adherence to precautionary measures against COVID-19, including wearing face mask, frequent handwashing, household disinfection, social distancing, minimising unnecessary travel, and stocking up on food and daily essentials.Results Of the 1030 participants, 166 (16.1%) had clinically significant mental health problems. Interestingly, they were more likely to stock up on food and daily essentials during the pandemic (7 (4.2%) vs 15 (1.7%), p=0.04; unadjusted OR=2.49, 95% CI=1.00 to 6.21, p<0.05) and had a lesser tendency to stop social distancing even if the pandemic subsides (86 (51.8%) vs 513 (59.4%), p=0.07; unadjusted OR=0.74, 95% CI=0.53 to 1.03, p=0.07). The latter association remained significant after adjusting for the confounding factors (adjusted OR=0.68, 95% CI=0.48 to 0.96, p=0.03).Conclusions Contrary to our hypothesis, people who are mentally unwell might go beyond the recommended precautionary measures. Our findings highlight the need to identify mental health problems and provide care and support for those who might go too far with precautionary measures.Trial registration number ChiCTR 2000033936.